KONSEP MARKETING DALAM MENINGKATKAN MINAT INPUT DI LEMBAGA PENDIDIKAN ISLAM - Moh Fachri; Laily Imzaqiyah (Perkumpulan Manajer Pendidikan Islam (PERMAPENDIS) Indonesia, 2019)
This paper discusses the concept of marketing in Islamic educational institutions. Along with the development of the times, the competitiveness of institutions of both Islamic education and not also increasingly developed and diverse. One of the main problems faced is the recruitment of new students each year. Each institution does a variety of ways to get the most students with certain strategies, one of which is to use marketing or marketing strategies. This paper is made by collecting data related to the title from various reference sources so that it concludes that marketing is an inseparable action from the efforts of Islamic educational institutions in increasing their input interest. However, from various existing marketing theories, Islamic educational institutions must be able to design marketing strategies that are unique and targeted so that they become differentiators from other marketing strategies.